2013
DOI: 10.1242/jeb.085332
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the expression and current of the Na+/K+ pump in the snail nervous system after exposure to static magnetic field

Abstract: +/K + pump current density was significantly increased after the 10mT SMF treatment. The SMF-induced increase was different in the two groups of control snail neurons, as defined by the pump current level. The results obtained could represent a physiologically important response of neurons to 10mT SMF comparable in strength to therapeutic applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…The increment in bioconductivity and permittivity of rat's kidney especially at 10 and 18 mT intensities immediately after SMF exposure may be due to disturbance in ion permeability and of kidney cell membrane but cannot be due to thermal effects of SMF as represented by [34,35]. It can be due to changes in electrical bioconductivity of some cell ions, such as Ca+, Na+ and K+ ions, as reported by [36][37][38] respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The increment in bioconductivity and permittivity of rat's kidney especially at 10 and 18 mT intensities immediately after SMF exposure may be due to disturbance in ion permeability and of kidney cell membrane but cannot be due to thermal effects of SMF as represented by [34,35]. It can be due to changes in electrical bioconductivity of some cell ions, such as Ca+, Na+ and K+ ions, as reported by [36][37][38] respectively.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, RBFOX3 gene encodes a member of the RNA-binding FOX protein family, which is involved in the regulation of alternative splicing of pre-mRNA. It has an RNA recognition motif domain, and is known to produce the neuronal nuclei (i.e., NeuN) antigen that has been widely used as a marker for post-mitotic neurons (see https://www.ncbi.nlm.nih.gov/gene/146713 ; see also Nikolić et al, 2013 where is reported to identify neural cells in Helix ).…”
Section: Discussionmentioning
confidence: 99%
“…The proposed mechanism of action involves increased local vascularity, vascular tone, alterations in the sodium potassium pump and decreases in histamine and carrageenan. 39,40 Several small studies have shown improvements in electrodiagnostic testing and pain scales with the use of magnetized wristbands. 4143 However, the research is preliminary, has methodological concerns, and only provides limited clinical information for treatment recommendations.…”
Section: Carpal Tunnel Syndromementioning
confidence: 99%